Biosensors in the small scale: methods and technology trends. Issue 1 (1st March 2013) - Senveli, Sukru U.; Tigli, Onur
Abstract : This study presents a review on biosensors with an emphasis on recent developments in the field. A brief history accompanied by a detailed description of the biosensor concepts is followed by rising trends observed in contemporary micro‐ and nanoscale biosensors. Performance metrics to quantify and compare different detection mechanisms are presented. A comprehensive analysis on various types and subtypes of biosensors are given. The fields of interest within the scope of this review are label‐free electrical, mechanical and optical biosensors as well as other emerging and popular technologies. Especially, the latter half of the last decade is reviewed for the types, methods and results of the most prominently researched detection mechanisms. Tables are provided for comparison of various competing technologies in the literature. The conclusion part summarises the noteworthy advantages and disadvantages of all biosensors reviewed in this study. Furthermore, future directions that the micro‐ and nanoscale biosensing technologies are expected to take are provided along with the immediate outlook.